'Rehabilitation' of M.N. Pokrovsky in the community of historians: Late 1950s – 1960s - V.S. Gruzdinskaya (Ученые записки Казанского университета: Серия Гуманитарные науки)
In the paper, the most important and resonant episodes of M.N. Pokrovsky’s “rehabilitation” as a researcher were studied. Based on the analysis of various published and unpublished sources, a number of conclusions were drawn. Firstly, the period of late 1950s – 1960s was marked by the rejection of the previous assessments of M.N. Pokrovsky’s legacy that became popular in the historiography of the Stalin era at the level of party and political discourses, as well as among researchers. Secondly, historians proposed different models for studying M.N. Pokrovsky’s legacy; the ubiquitous feature of all models was the use of archival sources. The “living memory” and personal experience of the academic community served as an integral supplement to the “cold” documentary facts. Thirdly, the active participation of Soviet historians in returning of M.N. Pokrovsky to the historiographic pantheon was of great importance. M.V. Nechkina, E.A. Lutsky, and A.L. Sidorov were among them. Interestingly, they were among the authors of an earlier published two-volume edition against M.N. Pokrovsky. At the same time, the limits of what was “acceptable” or not were still defined by the government authorities. This influenced the presentation of scientific knowledge to the professional community.